Comparison between 1.5 and 3-Tesla MRI findings in Ménière’s disease - Duarte, Juliana Antoniolli; Garcia, Marcio Ricardo Taveira; Souza, Soraia Ale; Monsanto, Rafael da Costa; Sarpi, Maira de Oliveira; Juliano, Amy; Gananca, Fernando Freitas (Frontiers in Neurology, 2024)
Introduction 3 T-MRI of the inner ear has been used to identify the endolymphatic hydrops (EH) phenomenon, and less frequently 1.5 T-MRI. The aim of this study was to assess whether there was agreement between findings of EH at 1.5 T MRI and those obtained at 3.0 T MRI in patients clinically diagnosed with definite Meniere disease (MD). Methods Cross-sectional, blinded study was conducted in a tertiary neurotology ambulatory practice. Thirty patients with clinical diagnosis of unilateral definite MD was included. Two MRI exams (1.5 T and 3.0 T) were performed for each patient and were evaluated by two examiners (E1, E2) who were blinded to the symptomatic ear. An analysis of intra-and inter-examiner agreement was performed. It was determined whether there was an association between MRI findings and disease duration, symptom severity, and MD clinical stage. Results E1 found EH at 3 T-MRI in 26 (86.66%) patients and at 1.5 T-MRI in 25 (83.33%). E2 found EH in 25 (83.33%) patients in 3 T-MRI and in 22 (73.33%) at 1.5 T-MRI. The agreement between the examiners’ assessments in relation to the EH was high (0.844) for the 3 T MRI and substantial for the 1.5 T, both statistically significant. There was no statistically significant relationship between EH imaging findings and clinical disease severity and course. Discussion 1.5 T and 3.0 T MRI images agreed regarding the findings of absence or presence of cochlear hydrops (CH) and vestibular hydrops (VH). The degrees of CH and VH found at 3.0 T MRI in symptomatic ear were not associated with clinical aspects and the stage of disease.